2011
DOI: 10.1124/mol.111.073759
|View full text |Cite
|
Sign up to set email alerts
|

Diflavin Oxidoreductases Activate the Bioreductive Prodrug PR-104A under Hypoxia

Abstract: The clinical agent PR-104 is converted systemically to PR-104A, a nitrogen mustard prodrug designed to target tumor hypoxia. Reductive activation of PR-104A is initiated by oneelectron oxidoreductases in a process reversed by oxygen. The identity of these oxidoreductases is unknown, with the exception of cytochrome P450 reductase (POR). To identify other hypoxia-selective PR-104A reductases, nine candidate oxidoreductases were expressed in HCT116 cells. Increased PR-104A-cytotoxicity was observed in cells expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
64
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 38 publications
2
64
1
Order By: Relevance
“…Advances in biomarker analysis of individual patients, whether based on tissue biopsies, serum or plasma samples, or circulating tumor cells, could be applied to patients and help guide decisions on TH-302 treatment based on POR or other activating enzymes identified. Population-level analysis of POR expression suggests a high frequency of expression in malignancies of the ovary and liver (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in biomarker analysis of individual patients, whether based on tissue biopsies, serum or plasma samples, or circulating tumor cells, could be applied to patients and help guide decisions on TH-302 treatment based on POR or other activating enzymes identified. Population-level analysis of POR expression suggests a high frequency of expression in malignancies of the ovary and liver (29).…”
mentioning
confidence: 99%
“…These results provide the basis for the development of diagnostic tests that could identify patients most likely to benefit from TH-302 based on their HDR status. For example, the potential prognostic value of the BRCA-like profile in ovarian carcinomas (45) may be of interest, particularly if associated with the observations of elevated POR expression (29). Likewise, cancer drugs that that have been shown to downregulate HDR, such as the approved agents gemcitabine, vorinostat, bortezomib, and imatinib (46)(47)(48)(49), may combine with TH-302 in additive or synergistic manners due to complementary mechanisms of action.…”
mentioning
confidence: 99%
“…6,10,11 The reduction of PR-104A under hypoxic conditions is catalyzed by members of the diflavin reductase family of proteins, especially NADPH:cytochrome P450 oxidoreductase (POR). 12,13 However, PR-104A is also activated in an oxygen-insensitive manner by human aldo-keto reductase 1C3 (AKR1C3). 14 This represents an off-target mechanism of activation in relation to the original drug design concept but may be exploitable in cancers with high AKR1C3 activity.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously analyzed AKR1C3 expression in 2700 tumors of 19 different types and a wide range of normal tissues, demonstrating that strong AKR1C3 expression was most prevalent in hepatocellular carcinoma (HCC) tumors. 14 The increased sensitivity of AKR1C3 staining in HCC relative to most normal tissues, coupled with the high expression of POR in many HCC biopsies 12 and evidence for hypoxia 15 suggested that PR-104 may have therapeutic utility in this clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From ester that is hydrolyzed in vivo to PR-104A, which is then metabolized under hypoxia by the 1-electron NADPH:cytochrome P450 oxidoreductase (CYPOR) and related flavoproteins to DNA cross-linking metabolites (PR-104H or PR-104M). 20 Unlike TH-302, PR-104A is also activated to PR-104H independently of hypoxia by aldo-keto reductase 1C3 (AKR1C3). 21 AKR1C3 is a member of a superfamily of NAD(P)H-linked oxidoreductases that reduce aldehydes and ketones to their corresponding primary and secondary alcohols.…”
Section: Introductionmentioning
confidence: 99%